Causality of Efficiency, Effectiveness and Independence to Financial Performance (Tidore City Case Study) - Prince Charles Heston Runtunuwu; Bakri Soamole; Nurlaila (Enrichment : Journal of Management, 2021)
The purpose of this study is: 1) To find out If Independence affects the financial performance of the government of Tidore Islands City. 2) To find out If Harmony affects the financial performance of the government of Tidore Islands City. 3). To find out if Efficiency affects the financial performance of the government of Tidore Islands City. 4) To find out If Effectiveness affects the financial performance of the government in Tidore Islands City? with analysis methods using financial ratio analysis tools. The results of this study suggest that: 1) The ratio of regional independence has not been able to optimize pad to finance regional development. Public awareness and participation in the payment of taxes and levies is also one of the things that causes pad produced by the Tidore City Government to be few and unreliable to finance development. In addition, there are also differences in the implementation of government and loans as well as assistance from the center and total revenue in each region and the realization of spending in each region. To overcome this, local governments must be able to optimize revenues from their existing revenue potential, initiatives and willingness to regional government is needed in an effort to improve PAD, such as the service of potential sector BOM. 2) Judging from the results of the analysis of the ratio of effectiveness of good performance in terms of realizing the planned PAD. Investigation in Tidore City, its financial management has also been effective. 3). Judging from the results of the analysis of the Efficiency Ratio that the Financial Performance of the Tidore City Government has not been efficient. 4). The ratio of harmony is the allocation of Operating Expenditures greater than the Capital Expenditure.